Expression of the oncogene of avian reticuloendotheliosis virus in Escherichia coli and identification of the transforming protein in reticuloendotheliosis virus T-transformed cells. - Herzog, N K (1986)
The genome of reticuloendotheliosis virus T (REV-T) includes a unique oncogene v-rel, which is transcribed in low amounts into a 3.0-kilobase subgenomic mRNA in REV-T-transformed lymphoid cells. To identify the v-rel protein, REV-T DNA sequences were cloned into bacterial plasmid vectors designed to achieve expression of foreign DNA sequences in Escherichia coli. Portions of the v-rel gene were joined to the 5' segment of the trpE gene. Upon induction of trpE with indoleacrylic acid, large amounts of trpE-v-rel fusion proteins were produced by the bacteria carrying these recombinant plasmids. Two trpE-v-rel fusion proteins were synthesized in E. coli, which collectively represent three-quarters of the predicted v-rel protein. Polyclonal antisera were generated to trpE-v-red fusion proteins. These antisera were used in immunoblotting experiments to identify a 57-kDa v-rel protein in REV-T-transformed lymphoid cells lines and REV-T-infected chicken embryo fibroblast cultures. The v-rel gene expressed in E. coli under lac control was found to produce a 56-kDa protein. Although REV-T-transformed and Marek disease virus-transformed lymphoid cells contain c-rel mRNA transcripts, a c-rel protein could not be detected with antisera directed against v-rel fusion proteins.